FORMATION OF STUDENTS' FUNCTIONAL LITERACY IS ONE WAY TO INCREASE PROFESSIONAL COMPETENCE - Akhmediyeva, Г.Б; Seitova, С.М.; Egemberdieva, С.Ш. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
One of the main problems of the modern school is the lack of qualified, competent personnel. Therefore, the article defines that the training of teachers in higher education institutions is mainly limited to considering the theory of subject education, pedagogy and methods of teaching the subject. Therefore, today it is necessary to focus the course of practice on the needs of a modern school. In order to improve the professional competence of school teachers, the process of determining their qualification compliance is changing. It is obvious that school education should be aimed at developing knowledge and skills in accordance with the concept of "lifelong learning". In the course of the study, the analysis of the concepts of competence, professional competence of mathematics teachers was carried out, and the identification of the main conditions for educating a competitive generation in accordance with modern requirements was carried out. The Strategic Development Plan of the Republic of Kazakhstan until 2025 provides for ways to improve the functional literacy of schoolchildren. In the course of the work, the results of a survey among teachers of mathematics and Natural Sciences on the topic "the role of professional competence in the development of functional literacy of students" were analyzed and conclusions were drawn. As a result, teachers identified ways to apply effective methods and techniques for developing students ' functional literacy and creative thinking. At the same time, ways to develop tasks aimed at developing functional literacy of students were considered. It is determined to design the educational process using tasks designed to develop mathematical and reading literacy, natural science literacy, and creative thinking of students. In order to solve these problems, the possibility of teaching an intra-school course for teachers "mechanism for compiling Mathematical, Natural and reading literacy tasks" for students of the specialty of mathematics was considered. Proved on the basis of the results of the experiment.